Economic Dimensions of Harvest Festivals in Odisha: Community Participation, Gender Roles and Livelihood Impacts - , Priyanka Kumari Nayak; , Ankit Yadav; , Bharath Kumar Mannepalli; , Prakhar Deep; , Virendra Kamalvanshi; , Saket Kushwaha (Archives of Current Research International, 2025)
This study explores the economic significance of harvest festivals in Odisha, with a focus on community participation, gender dynamics, and their impact on rural livelihoods. Using a mixed-method approach, both qualitative and quantitative data were gathered from 120 respondents in the Sundargarh district, specifically Bisra and Nuagaon taluks. The research examines how these festivals contribute to income generation, employment, and tourism. Findings reveal that harvest festivals serve as vital economic stimuli by promoting local markets, cultural performances, and artisanal goods. Income sources during festivals included handicrafts, traditional food items, handloom products, and cultural activities, contributing up to 35% of household annual income. Expenditure patterns showed the highest spending on food and clothing, indicating the socio-cultural importance of celebration. Gendered participation was evident: women were predominantly involved in cooking, decoration, and ritual practices, while men led ceremonies and agricultural tasks. Community involvement was multifaceted, ranging from collective dining to organizing cultural programs and supporting the resource-poor. The festivals also play a crucial role in social cohesion and cultural preservation, strengthening intergenerational and community bonds. Despite traditional gender roles, women’s contributions were central to the festival economy. The study concludes that harvest festivals are not only platforms of cultural expression but also engines of rural economic resilience. Policy support and structured promotion of such festivals could enhance their potential as sustainable development tools, fostering cultural tourism and inclusive rural growth.